Habitat selection by the black-tufted marmoset Callithrix penicillata in human-disturbed landscapes. (15th March 2018) - Secco, Helio; Grilo, Clara; Bager, Alex
Abstract: There are several primate species with high risk of extinction in small forest fragments disturbed by human activities. However, some species exhibit high ecological plasticity, which allows them to persist in human-modified landscapes. The main goal of this study is to examine the relative roles of vegetation (mean distance among trees and mean canopy cover), human disturbance (distance to the road, distance to the fragment edge and edge type), and habitat spatial configuration (spatial autocorrelation index, category of quadrat – position within the fragment/fragment type) on the habitat selection of the black-tufted marmoset Callithrix penicillata in forest patches. We selected forest patches near and away from roads/urban areas, in southern Minas Gerais state, south-eastern Brazil. We used generalized linear mixed models to explain the presence of black-tufted marmoset in those patches. Our results show that black-tufted marmoset tend to occupy forest fragments closer to roads/urban areas, and consequently are under the influence of anthropic disturbance. In addition to the area delimited by these fragments, there is a preference for edge environments, where disturbances are exacerbated and the ecological conditions are suitable for exploitation by the black-tufted marmoset (supply of gum trees and reduced risk of competition). We suggest that a cross-habitat spillover by marmoset occur from forests to small habitat patches close to human-modified areas, such as those in proximity to roads and urban zones.